2000
DOI: 10.1046/j.1365-2265.2000.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring serum insulin‐like growth factor‐I (IGF‐I), IGF binding protein‐3 (IGFBP‐3), IGF‐I/IGFBP‐3 molar ratio and leptin during growth hormone treatment for disordered growth

Abstract: OBJECTIVE Serum IGF‐I levels are monitored during GH replacement treatment in adults with GH deficiency (GHD) to guide GH dose adjustment and to minimize occurrence of GH‐related side‐effects. This is not routine practice in children treated with GH. The aim of this study was to evaluate changes in (1) serum IGF‐I, IGFBP‐3 and IGF‐I/IGFBP‐3 molar ratio, and (2) serum leptin, an indirect marker of GH response, during the first year of GH treatment in children with disordered growth. DESIGN An observational pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 47 publications
(61 reference statements)
8
36
2
Order By: Relevance
“…Short-term changes in serum leptin levels have been found to show correlation with height response [16, 17]. However, in our study, although IGF-I increased and leptin decreased on GH therapy, there were no correlations between changes in leptin and IGF-I and change in height.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Short-term changes in serum leptin levels have been found to show correlation with height response [16, 17]. However, in our study, although IGF-I increased and leptin decreased on GH therapy, there were no correlations between changes in leptin and IGF-I and change in height.…”
Section: Discussioncontrasting
confidence: 55%
“…In the study by Tillmann et al [17] leptin levels decreased in GH-deficient children on GH therapy and not in non-GH-deficient children. In the study by Kriström et al [16] the marked decrease in leptin levels on GH therapy was evident in the first 3 months in GH-deficient and non-GH-deficient children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kriström et al [26] 58% of the variation in the 1 st year growth response to GH therapy might be explained by serum levels of IGF-I and IGFBP-3 before treatment, and their increase during GH therapy. Conversely, Tillmann et al [27], as well as Lanes and Jakubowicz [28] did not confirm any relationship between HV during GH therapy and IGF-I and IGFBP-3 concentrations. In 2005, Ranke et al [29] reported a negative correlation between HV in the initial phase of GH treatment and IGF-I SDS before GH therapy, however with no correlation between HV during the therapy and the increase of IGF-I secretion.…”
Section: Discussionmentioning
confidence: 95%
“…The determination of IGF-I and IGFBP-3 serum levels has been widely used as screening parameters in the evaluation of growth disorders. In addition to diagnosis of GH deficiency or GH excess, serum levels of IGF-I and IGFBP-3 are used for monitoring the therapy in both conditions [11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%